The Impact of the COVID-19 Pandemic on Depressive Symptoms in China: A Longitudinal, Population-based Study - Yi Zhou; Weicheng Cai; Liyang Xie (International Journal of Public Health, 2022)
Objectives: We aimed to examine how COVID-19 incidence is associated with depressive symptoms in China, whether the association is transient, and whether the association differs across groups. Methods: We used a longitudinal sample from 2018 and 2020 waves of the China Family Panel Study. We constructed COVID-19 incidence rates as the number of new cases per 100,000 population in respondents’ resident provinces in the past 7, 14, and 28 days when a respondent was surveyed. We performed linear or logistic regressions to examine the associations, and performed stratified analyses to explore the heterogeneity of the associations. Results: Our sample included 13,655 adults. The 7-day incidence rate was positively associated with the CES-D score (coef.=2.551, 95% CI: 1.959-3.142), and likelihood of being more depressed (adjusted odds ratio=6.916, 95% CI: 4.715–10.144). The associations were larger among those with less education, pre-existing depression, or chronic conditions. We did not find any significant association between the 14- or 28-day local incidence rates and depressive symptoms. Conclusion: The impact of COVID-19 incidence on mental health in China’s general population was statistically significant and moderate in magnitude and transient. Disadvantaged groups experienced higher increases in depressive symptoms.